PENGARUH LAMA SIMPAN PADA VIGOR BENIH DAN KECAMBAH SORGUM (Sorghum bicolor [L.] Moench) GENOTIPE KAWALI DAN P/F-10-90A - Iska Hartina Anggraini; Muhammad Kamal; Eko Pramono; Kukuh Setiawan (Jurnal Agrotek Tropika, 2020)
Sorghum is a type of carbohydrate-producing serelia plant. Sorghum has a great potential to be developed in Indonesia.  Seed storing time is the time period of the seed storage before the seed is planted again, while the storage of the seed is carried out with the aim of maintaining seed viability in the save period for as long as possible and can be used for the next planting period.  The purpose of this study was to determine the effect of storage time on seed vigor and sprouts of Kawali and P/F-10-90A genotypes. This research was conducted at the Laboratory of Seed and Plant Breeding, Faculty of Agriculture, University of Lampung, Bandar Lampung which runs from February 2017 until February 2018. This study uses split plot design with 3 group replications. The main plot is the storage time (LS) that was consisted of 0, 4, 8 and 12 months storage time period. Subplot is genotype (G), which consists of Kawali (G1 ) and P / F-10-90A (G2). The results showed that seed vigor and sprouts decreased significantly at 4 and 8 months storage time with the percentage of dead seeds 16.7% and 40.7%, while the percentage of normal strong sprouts at 4 months amounted to 74% for genotype P/ F-10-90A  and 8 months 54% for genotype Kawali.  P/F-10 -90A genotypes have higher seed vigor and sprouts vigor compared to Kawali genotypes as indicated by dead seed variables, strong normal sprouts, normal sprout length canopy, long root primary roots, normal sprouts, dry weight normal sprouts, and normally strong sprouts. The effect of interaction  between storage time and genotype was shown by seed vigor of genotype P/F-10-90-A seedlings which were proven to be superior for 4, 8 and 12-month storage time period.  Excellence of genotype P/F-10-90-A make it can be stored and was allowed to be used as good seed on next season farming.